Analisis Komparasi Problem Based Learning Dengan Team Assisted Individualization Pada Penguasaan Kompetensi “Mekanisme Katup & Sistem Bahan Bakar” Kelas XI SMK - Holis Harifi; Djoko Adi Walujo; Sugito (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
Vocational school as a vocational school is different from other public high schools. Put more emphasis on competence or expertise. Monotonous learning is not varied, boring and is more centered on the teacher, causing ineffective and unpleasant. This study uses a Class Action Research (CAR) approach aimed to find out how the comparative analysis of PBL and TAI is effective in mastering the competence of